Determinantes de participação política e sustentabilidade ambiental em assentamentos rurais do Distrito Federal e entorno - da Silva, Luciano Pereira (2015)
The aim of this paper was to find the variables that determine the environmental and political behavior of settled agrarian reform Gifts rural settlements of the Federal District and its surroundings. For this, the measurement of environmental and political behavior of the settlers, we inferred, by calculating the Environmental Sustainability Index - ISA and Political Participation Index - PPI, and to find the determinants econometric models of multiple linear regression were used, estimated by OLS. In short, there were significant correlations between an outstanding environmental performance and the level of politicization of the settlers. These behaviors were best determined when it promoted the interaction between variables, trying to maximize potential characteristics of the settlers. Then it is concluded that the policies and actions directed to the local development of these agents should be linked to integrated rural development and enhanced through projects lined in Environmental Sustainability and Effective Political Participation of the settlers.